2006
DOI: 10.12693/aphyspola.110.817
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Response of Metal - Porous Silicon Structures to Microwave Radiation

Abstract: Structures containing layers of porous silicon with two metal contacts are investigated. Porous silicon is manufactured by anodizing p-type crystalline silicon plates of resistivity of 0.4 Ω cm. Contacts for the samples are made by additional boron doping of the surface and by thermal evaporation of aluminium. Resistance and current-voltage characteristics are investigated. Response of the porous silicon layer containing structures under action of pulsed microwave radiation was investigated for the first time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Quantum confinement effect is absent in PSiL1 layer due to its lower porosity, i. e. higher crosssectional dimensions of the silicon stem, compared to those of the PSiL2. As photoluminescence investigations have shown, the forbidden energy gap of PSiL2 layer lies in the range of 1.6-1.9 eV, i. e. is wider than that of c-Si because of quantum confinement effect [6][7][8][9]. The quantum confinement effect which is present in a stem of the PSiL2 layer indicates that the cross-section of the stem should be in the range of few nanometres [1,2].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Quantum confinement effect is absent in PSiL1 layer due to its lower porosity, i. e. higher crosssectional dimensions of the silicon stem, compared to those of the PSiL2. As photoluminescence investigations have shown, the forbidden energy gap of PSiL2 layer lies in the range of 1.6-1.9 eV, i. e. is wider than that of c-Si because of quantum confinement effect [6][7][8][9]. The quantum confinement effect which is present in a stem of the PSiL2 layer indicates that the cross-section of the stem should be in the range of few nanometres [1,2].…”
Section: Resultsmentioning
confidence: 99%
“…The basic layer of porous silicon PSiL2 was formed in the second phase of the etching process. Its thickness was about 5-20 µm and porosity reached 75% [1][2][3]7]. The thickness of the basic PSiL2 layer was varied by choosing the etching time; thus resistance of the sample was controlled.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considerable quantity of interesting works was devoted to create a silicon radiator by means of cheap porous silicon technology [4,5]. A series of recent works was executed on the research of influence of microwave radiation * corresponding author; e-mail: eusat@vgtu.lt on the properties of porous silicon structures [6,7]. It was revealed that the structures had by several orders higher sensitivity to microwave radiation than similar semiconductor structures without a porous layer.…”
Section: Introductionmentioning
confidence: 99%